Urinary Prostaglandin E in Patients with Hypertension: Relationship to R, enin-Angiotensin-Aldosterone System - Yasujima, M.; Yoshinaga, K.; Sate, M.; Abe, K.; Sakurai, Y.; Irokawa, N.; Chiba, Satoru; Ito, T.; Otsuka, Y.; Haruyama, T. (The Japanese Journal of Nephrology, 1980)
The interrelationship between Renin-Angiotensin-Aldosterone (R-A-A) system and renal prosta-glandin E (PGE) was studied in essential hypertension and primary aldosteronism. Urinary PGE, converted to PGB before extraction, was measured by radioimmunoassay using PGE antiserum. The accuracy and reproducibility of this method was excellent enough to determine the level of urinary PGE. Urinary excretion of PGE was significantly decreased in patients with essential hypertension and primary aldosteronism compared with that of normal subjects. In essential hypertension and normal subjects, there was no significant correlation between plasma reamn activity (PRA) and urinary excretion of PGE but a significant positive correlation was found between urinary excretion of sodium and that of PGE. Urinary excretion of PGE was not decreased in low renin essential hyper-tension. No obvious relationship was observed between the changes in PRA and urinary excretion of PGE during the stimulation of renin release. After the restriction of sodium intake urinary ex-cretion of PGE was significantly decreased in spite of the marked increase in PRA and plasma aldo-sterone concentration (PAC). These data does not support that R-A-A system is the main regu-lator of renal PGE synthesis. It was suggested that renal PGE may play a role in renal sodium handling. In primary aldosteronism, aldosterone antagonist which reduced the urinary excretion of kallikreinn in our previous experiment did not decrease the urinary excretion of PGE, suggesting no direct relationship between renal kallikrein-kinin system and renal PGE synthesis in man. Thus, aldo sterone may not stimulate the renal PGE synthesis, though it activates the renal kallikrein-kinin system. In essential hypertension, R-A-A system was activated by the administration of furosemide and low sodium diet. The addition of indomethacin significantly decreased the urinary excretion of PGE and reduced the enhanced PRA and PAC to control level. It was suggested that the renal prostaa glandins play an imporsant role in renin release.